2010
DOI: 10.1007/s00018-010-0521-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two functional nuclear localization signals mediating nuclear import of liver receptor homologue-1

Abstract: Liver receptor homologue-1 (LRH-1) is a member of the nuclear receptor superfamily. We characterized two functional nuclear localization signals (NLSs) in LRH-1. NLS1 (residues 117-168) overlaps the second zinc finger in the DNA binding domain. Mutagenesis showed that the zinc finger structure and two basic clusters on either side of the zinc finger loop are critical for nuclear import of NLS1. NLS2 (residues 169-204) is located in the Ftz-F1 box that contains a bipartite signal. In full-length LRH-1, mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…, 2001; Lange et al. , 2007; Yang et al. , 2011), which is shared with the TbNup92 kinetoplastid orthologues (Figure 1 and Supplemental Figure S2A).…”
Section: Resultsmentioning
confidence: 99%
“…, 2001; Lange et al. , 2007; Yang et al. , 2011), which is shared with the TbNup92 kinetoplastid orthologues (Figure 1 and Supplemental Figure S2A).…”
Section: Resultsmentioning
confidence: 99%
“…IP and IB were performed essentially as described elsewhere (44). Cells were lysed by IP lysis buffer (20 mM Tris-HCl at pH 7.5, 0.5% NP-40, 150 mM NaCl, and protease inhibitors) (catalog P8340, Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the transition of Lrh-1 cellular localization from the nucleus to the cytoplasm abolishes the activation of cyp19a1a by Lrh-1 and related signals, and may represent an important mechanism for the down-regulation of cyp19a1a expression in the follicular cells of the mature ovary of the orange-spotted grouper and possibly other teleosts as well. It has been shown that disruption of the two nuclear localization signals (NLSs) in rat LRH-1 resulted in the cytoplasmic accumulation of LRH-1 [24] and phosphorylation of Ser72 by Akt within the putative NLS of Skp2 promoted its cytoplasmic translocation [36]. Because putative phosphorylation could be predicted at Tyr48 and Thr61 within NLS1 of the orange-spotted grouper Lrh-1 (with the online software NetPhos 2.0, for example), it is possible that modifications, most likely phosphorylation, of NLSs in the orange-spotted grouper Lrh-1 may also be involved in the cytoplasmic sequestration of Lrh-1 in the follicular cells of the mature ovary.…”
Section: Discussionmentioning
confidence: 99%
“…The orange-spotted grouper Lrh-1 homologue shared the typical structures of the nuclear receptor of Nr5a subfamily (Supplemental Fig. S1), namely the conserved DNA-binding regions (I and Ftz-f1 box), ligandbinding regions (II and III), the activation function-2 (AF-2) hexamer, and two nuclear localization sequences (amino acid residues 24 to ;75 for NLS1 and 76 to ;111 for NLS2) as in the rat [24]. Phylogenetic analysis categorized the orangespotted grouper Lrh-1 homologue to the Nr5a2 subfamily (Supplemental Fig.…”
Section: Sequence Analysis Of the Orange-spotted Grouper Lrh-1mentioning
confidence: 99%